Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam Siswa Sekolah Dasar - Irnawati Irnawati; Yusrizal Efendi; Mega Adyna Movitaria (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This article aims to describe the improvement of learning outcomes for Religious Education and Character Education (PAIdBP) by using the Problem Based Learning model in class V UPTD SDN 01 Mungka. The type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The research subjects were 22 students of class V UPTD SDN 01 Mungka. The data in this study are student learning outcomes at the end of each cycle. The resulting data is processed and analyzed descriptively qualitatively. The conclusion of the study shows that the use of the Problem Based Learning model can improve student learning outcomes in PAIdBP learning, this can be seen from the student learning outcomes in the first cycle, which is 80.44 increasing to 85.06 in the second cycle.